1995
DOI: 10.1096/fasebj.9.8.7768354
|View full text |Cite
|
Sign up to set email alerts
|

Caco‐2 cells as a model for intestinal lipoprotein synthesis and secretion

Abstract: Caco-2 cells, an intestinal cell line derived from a human colorectal carcinoma that spontaneously differentiates under standard culture conditions, lends itself to the in vitro study of human gut in view of its efficient intestinal transport processes. Among its multiple biological functions are those related to the absorption, transport, and metabolism of lipids and lipoproteins. Despite their intestinal origin, confluent Caco-2 cell monolayers primarily express L-FABP for the uptake of apical dietary long c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
151
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 191 publications
(157 citation statements)
references
References 61 publications
5
151
0
1
Order By: Relevance
“…Whether apoB-48 is degraded by proteasome-mediated events in intestinal cells is unknown. We initiated this study to examine the biogenesis of apoB-100 and apoB-48 in a model human intestinal cell line, CaCo2, that has been used extensively to study apoB biogenesis in the past (25). To our surprise, we found that newly synthesized apoB-100 and apoB-48 are quantitatively recovered in the cellular lysate and the medium in CaCo2 cells and do not seem to be subject to proteasome-mediated degradation.…”
mentioning
confidence: 99%
“…Whether apoB-48 is degraded by proteasome-mediated events in intestinal cells is unknown. We initiated this study to examine the biogenesis of apoB-100 and apoB-48 in a model human intestinal cell line, CaCo2, that has been used extensively to study apoB biogenesis in the past (25). To our surprise, we found that newly synthesized apoB-100 and apoB-48 are quantitatively recovered in the cellular lysate and the medium in CaCo2 cells and do not seem to be subject to proteasome-mediated degradation.…”
mentioning
confidence: 99%
“…Additionally, the incubation with EGF at a concentration of 1 nM (6 ng/mL) at least for 4 days significantly increased intracellular triglyceride content in mouse differentiated adipocytes (3T3-L1 cells) by stimulating acyl-CoA synthetase activity, which is the rate-limiting enzyme for adipogenesis (20). Because confluent Caco-2 monolayers primarily express intestinal fatty acid-binding protein for the uptake of long chain fatty acids (14), exogenous linoleic acid can serve as a substrate for lipid synthesis. Similarly, van Greevenbroek et al demonstrated that the addition of 14 C-linoleic acid was efficiently incorporated into triglycerides by Caco-2 cells (17).…”
Section: Discussionmentioning
confidence: 99%
“…The C2BBe1 cell line, cloned from human colon adenocarcinoma Caco-2 cells, has high homology in morphology compared with Caco-2 cells that was often used as an experimental model for the synthesis, absorption, or transport of macronutrients, minerals, vitamins, or drugs in the intestine (14,15). It is unclear whether linoleic acid also serves a regulatory function in the action of EGF on lipogenesis in the intestinal cells.…”
Section: Introductionmentioning
confidence: 99%
“…Nos observations suggèrent une fonction différente pour les deux : la L-FABP serait probablement chargée de faire converger les AGCL vers le réticulum endoplasmique (RE) pour la formation et la sécrétion des chylomicrons (CM) puisque peu de ces particules sont libérées par les cellules Caco-2 connues pour leur déficience en L-FABP [25,26]. De son côté, la I-FABP ne semble pas prêter son concours à cette voie et semblerait guider les AGCL vers d'autres compartiments intracellulaires.…”
Section: Facilitation Du Trafic Des Ag Par Les Protéines Cytosoliquesunclassified